TOURMALINE MAGNETIC SOCKS DAN ROM AKTIF UNTUK MENINGKATAN KEKUATAN OTOT PASIEN STROKE NON HEMORAGIK - Komul, Marsha; Suharsono, Suharsono; Pujiastuti, Rr Sri Endang (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
Non-hemorrhagic stroke occurs due to blockage in the blood vessels of the brain. This study aims to analyze the effect of combination intervention of Tourmaline Magnetic Socks and active ROM on increasing muscle strength in non-hemorrhagic stroke patients. The population in this study were all patients who suffered from non-hemorrhagic stroke. This research method uses quasi experimental pre-post test nonrandomized control group design, with a total of 60 respondents using the Simple Random Sampling technique. This research was carried out for 2 weeks with a frequency of 3 times a week with an administration time of 20 minutes. The data that has been obtained is then analyzed using univariate analysis (frequency distribution) and bivariate analysis (Wilcoxon test & Mann-Whitney Test). In both the control group and the intervention group, the majority of respondents experienced recurrent stroke once, namely 53 respondents. It is known that based on a test of the effect of the combination of Tourmaline Magnetic Socks and active ROM on delta muscle strength in the two groups, the value of P = 0.010. Muscle strength in the intervention group increased after being given Tourmaline Magnetic Socks and active ROM treatment with a value of ρ = 0.000, while muscle strength in the control group increased with a value of ρ = 0.003. The combination of Tourmaline Magnetic Socks and active ROM influences increased muscle strength in non-hemorrhagic stroke patients. it is recommended that non-hemorrhagic stroke patients consider incorporating Tourmaline Magnetic Socks and active ROM into their rehabilitation routine.